Validity of the Tree Drawing Test Suicide Ideation Assessment Scale in adolescents - Zhang, Yanfei; Liu, Yige; Liu, Wei; Sun, Lvping; Leng, Feng; Li, Ziyang; Liu, Guorui (Frontiers in Psychiatry, 2025)
ObjectiveTo examine the validity of the Tree Drawing Test Suicide Ideation Assessment Scale (TDT-SIAS) for screening suicidal ideation in adolescents.MethodsA case–control design was employed, involving 36 adolescents with suicidal ideation and 58 adolescents without suicidal ideation. All participants completed the Tree Drawing Test, and their responses were analyzed using computer-based image recognition and data acquisition techniques with the TDT-SIAS. Statistical analyses were then conducted.ResultsSignificant differences were observed in total scores between the suicidal ideation group and the non-suicidal group (p < 0.001). Using a cutoff score of 9, the Youden Index was 0.901, with a sensitivity of 0.935, specificity of 0.966, positive predictive value of 0.956, and negative predictive value of 0.949. Inter-rater reliability (Cohen’s kappa) ranged from 0.779 to 0.961.ConclusionThe TDT-SIAS demonstrated good screening performance and effectively distinguished adolescents with suicidal ideation from those without. It may serve as a preliminary screening tool for adolescent suicidal ideation. However, limitations of this study include the relatively small sample size and the lack of consideration for cultural differences, which may affect generalizability. Future studies should expand sample size and examine cross-cultural applicability.